Parents’ Understanding the Impact of Digital Platform on Students’ Learning - Jonner Simarmata; Evi Adriani (Edumedia Solution, 2026)
The development of digital technology has transformed the educational landscape, including the increased use of online learning platforms, which has led to a decline in interest in non-formal educational institutions. This community service (PKM) activity aims to increase students' and parents' understanding of the impact of digital technology on education and to revitalize interest in taking English courses at LB-LIA Jambi. The method used was an interactive lecture with a participatory approach. Results showed increased participant understanding and positive changes in attitudes toward face-to-face learning. This activity also emphasized the importance of digital literacy and institutional collaboration in addressing educational disruption